2021
DOI: 10.1002/asia.202100910
|View full text |Cite
|
Sign up to set email alerts
|

Polarised Optical Emission from Organic Anisotropic Microoptical Waveguides Grown by Ambient Pressure Vapour‐deposition

Abstract: Ambient pressure chemical vapour deposition of 5,5′‐bis((2‐(trifluoromethyl)phenyl)ethynyl)‐2,2′‐bithiophene provides ultrapure needle‐shaped crystals. The crystal‘s supramolecular structure consists of an array of hydrogen bonds and π‐π interactions leading to anisotropic arrangements. The cyan emitting crystals exhibit an optical waveguiding tendency with guided polarised optical emissions due to anisotropic molecular arrangements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…The calculation of the OLC was carried out through the equation I=I 0 e À αx , where I is the PL intensity in the output, I 0 in the input, x is the propagation distance in the crystal and α the parameter to determinate in μm À 1 (Figure 7b). After conversion α to dB μm À 1 (by using the relation α (dB μm À 1 ) = 4.34 α (μm À 1 )), the value calculated for OLC is 1.13×10 À 2 dB μm À 1 , that is in the order of the best derivatives reported, [38][39][40] corroborating the good efficiency of this optical waveguide.…”
Section: Self-assembling Studiessupporting
confidence: 61%
“…The calculation of the OLC was carried out through the equation I=I 0 e À αx , where I is the PL intensity in the output, I 0 in the input, x is the propagation distance in the crystal and α the parameter to determinate in μm À 1 (Figure 7b). After conversion α to dB μm À 1 (by using the relation α (dB μm À 1 ) = 4.34 α (μm À 1 )), the value calculated for OLC is 1.13×10 À 2 dB μm À 1 , that is in the order of the best derivatives reported, [38][39][40] corroborating the good efficiency of this optical waveguide.…”
Section: Self-assembling Studiessupporting
confidence: 61%
“…The analysis of these crystalline aggregates confirms that the crystals with porous structures and internal channels showed waveguiding activity (Fig. S9-S12, ESI †) 43,44,48,49 while the crystals without internal channels and with compact structures do not behave as optical waveguides (Fig. S13, ESI †).…”
Section: Structure-waveguiding Relationshipmentioning
confidence: 68%
“…For this purpose, methoxy and CF 3 groups have been introduced at different positions of the carbon backbone, since in previous studies by our research group they have shown a great ability to form supramolecular aggregates. 43–46,49…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations